Menciptakan Suasana Perjumpaan Antar-Agama: Refleksi Filosofis Etika Global Hans Küng : Creating an Inter-Religious Meeting Atmosphere: Philosophical Reflections on Global Ethics Hans Küng - Marz Wera (Jurnal Teologi Amreta (ISSN: 2599-3100))
Indonesia faces the problem of differences for many year ago until now. Even though, Pancasila symbolizes the unity but mostly in religious relationship have a cliff between ''us’’ and ‘’them’’ for many reasons recently. Another problem emerges in area of Religious pluralism, makes the situation more difficult. The reality of religious diversity is isolated by misleading and shallow interpretations. The space for dialogue is insulated by religious formalism and theological claims of truth. The dialogue of agreement, both inclusivism and pluralism, has not been able to knit religious plurality. Traditions, symbols, rituals, ethical dimensions and universal core in religious dialogue as a precondition do not find space. In this context, the author is trying to offer the idea of "Global Ethics" by Hans Küng as a new understanding of religious dialogue. === Indonesia menghadapi masalah perbedaan selama bertahun-tahun yang lalu hingga sekarang. Meskipun Pancasila melambangkan persatuan, tetapi sebagian besar dalam hubungan agama memiliki jurang antara '' kami 'dan' mereka 'karena banyak alasan baru-baru ini. Masalah lain muncul di bidang pluralisme agama, membuat situasi lebih sulit. Realitas keragaman agama diisolasi dengan interpretasi yang menyesatkan dan dangkal. Ruang untuk dialog terisolasi oleh formalisme agama dan klaim kebenaran teologis. Dialog kesepakatan, baik inklusivisme dan pluralisme, belum mampu merajut pluralitas agama. Tradisi, simbol, ritual, dimensi etis, dan inti universal dalam dialog keagamaan sebagai prasyarat tidak menemukan ruang. Dalam konteks ini, penulis menawarkan ide "Global Ethics" oleh Hans Küng sebagai pemahaman baru tentang dialog agama.